Sudden Cardiac Death (SCD) in Young Athletes – A Review of Current Guidelines and Key Studies - Żmigrodzka, Anna; Przepióra, Agnieszka; Orłowska, Maria; Kozłowska, Jana; Sanocka, Maria; Wielogórska, Aleksandra; Trojnar, Karolina; Czernic-Goławska, Klaudia; Kamińska, Agnieszka; Falana, Joanna; Kwiatkowska, Anna (Quality in Sport, 2026)
Background: Sudden cardiac death (SCD) in young athletes is a rare but catastrophic event that exerts a profound impact on the medical community, athletic organizations, and society. While regular physical activity provides robust cardiovascular benefits, vigorous exertion can act as a trigger for fatal arrhythmias in individuals with underlying and often clinically silent structural or electrical cardiac abnormalities. Aim: The objective of this study is to synthesize current epidemiological data, explore the pathophysiological etiologies of SCD in young athletes, evaluate ongoing debates regarding screening modalities, and outline the contemporary clinical framework—emphasizing the shift toward Shared Decision-Making and robust secondary emergency prevention. Material and methods: This comprehensive narrative review synthesizes data from modern prospective investigations utilizing mandatory reporting systems, such as the National Collegiate Athletic Association databases and the US Registry for Sudden Death in Athletes, as well as a comparative analysis of the latest international guidelines (HRS 2024, ACC/AHA 2025). Results: The incidence of SCD is highly variable across subpopulations, demonstrating significant disparities based on sex, race, and sporting discipline, with the highest risk identified in Black male basketball players,. Key etiologies include structural conditions like HCM and ACM, autopsy-negative findings linked to channelopathies, and mechanical triggers such as commotio cordis,,. Furthermore, the evolution of ECG interpretation criteria has improved specificity, reducing false-positive rates to between 1.3% and 3%. Conclusions: There is a paradigm shift away from paternalistic disqualification toward Shared Decision-Making, allowing many athletes to safely return to play while emphasizing the rigorous implementation of Emergency Action Plans and rapid access to automated external defibrillators as the most effective survival interventions.